O uso indiscriminado de antimicrobianos afeta a minha saúde? uma proposta de abordagem investigativa para o ensino médio - Marlise Aparecida de Oliveira Martins (2022)
Health as seen in the National Curriculum Parameters, is presented as a dynamic balance of the body, whereas the National Common Curriculum Base defends the perception that the human body is a dynamic and articulated whole. According to the World Health Organization, to be healthy is to be in a state of complete physical, mental and social well-being and not merely the absence of disease. Therefore, this theme is related to technical-scientific development and its teaching has been a challenge for education regarding the guarantee of effective learning for health promotion. The subject of health can be worked on in the school environment in an investigative and transversal way in all disciplines, since its importance lies within everyday life, enhancing the resolution of daily problems, and preparing students to transform their reality. Among the many approaches to this topic highlights the use of medicine by the population. A relevant theme due to the lack of knowledge about what health actually is, leads to a process of medicalization of life, the indiscriminate use of antimicrobials is the main factor responsible for bacterial resistance and the emergence of superbugs. Thus, it is also the school's duty to develop critical, reflective and educational actions that promote health. In addition to it, Digital Information and Communication Technologies have been inserted into teaching practices to promote more meaningful learning through the implementation of active teaching methodologies, aligning the teaching-learning process with the reality of students and awakening greater interest and engagement of students in all stages of education through more dynamic, interactive and collaborative classes. Using research-based Science Teaching as a pedagogical strategy, the objective of this proposal for a didactic sequence (DS) is to stimulate, promote and value student protagonism, embracing the theme of the de-medicalization of life in the context of health promotion and scientific literacy on the basic concepts of antimicrobials, antimicrobial resistance and microbiology; and also to stimulate the creation of publicity materials, for the dissemination of information on the conscious use of antimicrobials. The DS proposed and defended here comprises six stages composed of nine classes based on the investigation cycle and its phases. It should be evaluated in a procedural way, taking into account the participation of students, at each stage, with notes in logbooks, questionnaires on prior knowledge, conversation circles and encouraging the development of dissemination materials. It is important to observe the students' assimilation, interaction and difficulties in relation to the investigative approach, identifying scientific literacy, understanding of the nature of Science and the ethical and political factors that surround its practice and understanding of the existing relationships between Science, Technology, Society and Environment.